Tensile behaviour of headed anchored hollo-bolts in concrete filled hollow steel tube connections. (1st May 2021) - Debnath, Partha Pratim; Chan, Tak-Ming
Highlights: Investigation on tensile behaviour of hollo-bolted connections with CFST columns. FE models have been generated for validation and conducting parametric studies. Holistic behavior of EHB-CFST connection with varied combination is studied. FE models can predict accurately behavior of single bolted CFST connections. New observations that counter and complement previous findings. Abstract: Achieving a strong and stiff bolted connection with concrete filled steel tube (CFST) has been a challenge to structural engineers, and therefore to enhance the connection performance, blind-bolts that are extended to anchor in the concrete core have been recently developed. Though some experimental tests to investigate the performance of extended blind-bolts were conducted, a holistic understanding of extended hollo-bolts remains to be at scarce because of certain limitations in the experimental program. In this work, the tensile pull-out behaviour of extended hollo-bolt, has been extensively investigated for its performance with CFST column connections. The study is conducted initially by validating numerical models with existing experimental works, and later by conducting extensive finite element parametric studies to predict and understand the influence of various connection components. It is observed that, not only the presence of concrete in the hollow steel tube has led to reduced deformation of the connection, but also the bolt embedment length into the concrete core has significantly improved the strength and stiffness. The study observes significant change in connection behaviour due to influence of change of parameter profiles. In this study, the various failure modes that can be altered as per combinations of the connection component strength are elaborately discussed.